2013
DOI: 10.1155/2013/256043
|View full text |Cite
|
Sign up to set email alerts
|

Glucose Toxic Effects on Granulation Tissue Productive Cells: The Diabetics’ Impaired Healing

Abstract: Type 2 diabetes mellitus is a metabolic noncommunicable disease with an expanding pandemic magnitude. Diabetes predisposes to lower extremities ulceration and impairs the healing process leading to wound chronification. Diabetes also dismantles innate immunity favoring wound infection. Amputation is therefore acknowledged as one of the disease's complications. Hyperglycemia is the proximal detonator of systemic and local toxic effectors including proinflammation, acute-phase proteins elevation, and spillover o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
105
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(108 citation statements)
references
References 125 publications
2
105
0
1
Order By: Relevance
“…The extracellular matrix represents the granulation tissue that provides support for inflammatory cells, fibroblasts, and endothelial cells, and allows for the chemotaxis of epithelial cells (Hanson et al, 2005). Fibroblasts and endothelial cells are main targets of hyperglycemia in the granulation tissue (Berlanga-Acosta et al, 2013). Studies have shown that high glucose disrupt normal fibroblast physiology and derange the secretion of extracellular matrix ingredients (Hehenberger & Hansson, 1997;Rowe, Starman, Fujimoto, & Williams, 1977;Yevdokimova, 2003).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The extracellular matrix represents the granulation tissue that provides support for inflammatory cells, fibroblasts, and endothelial cells, and allows for the chemotaxis of epithelial cells (Hanson et al, 2005). Fibroblasts and endothelial cells are main targets of hyperglycemia in the granulation tissue (Berlanga-Acosta et al, 2013). Studies have shown that high glucose disrupt normal fibroblast physiology and derange the secretion of extracellular matrix ingredients (Hehenberger & Hansson, 1997;Rowe, Starman, Fujimoto, & Williams, 1977;Yevdokimova, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that high glucose disrupt normal fibroblast physiology and derange the secretion of extracellular matrix ingredients (Hehenberger & Hansson, 1997;Rowe, Starman, Fujimoto, & Williams, 1977;Yevdokimova, 2003). As depicted for fibroblasts, high glucose exerts a toxic effect on endothelial cells (Berlanga-Acosta et al, 2013). High glucose concentrations has been shown to disturb endothelial cell cycle, increase DNA damage, and delay endothelial cells replication, as inducing excessive cell death (Busik, Mohr, & Grant, 2008;Callaghan, Ceradini, & Gurtner, 2005;Hink et al, 2001;Rai et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…At the long term response (21 days after initiation) EGF induces the expression of a constellation of other growth factors that contribute to the healing process. In other words, the locally infiltrated EGF restores the deficit of growth factors brought about by diabetes and resumes the activity of tyrosine kinase receptors which appear crucial for the healing process, especially in the diabetic context where they are depressed [145].…”
Section: The Rationale For a Novel Delivery Procedure Egf Intralesiomentioning
confidence: 99%
“…However, a compromised inflammatory response associated with diseases such as diabetes (a prevalent co-morbidity particularly in the older population with type 2 diabetes; discussed in Purkayastha and Cai, 2013 (12); Hellman et al, 2012 (13); Mirza et al, 2013 (14)), can exert a negative effect on healing, leading to chronic wounds and life-threatening complications (15). Oppositely, excessive or unregulated inflammation may result in abnormal healing, with fibrosis or disruption of the integrity of the tissue function (16).…”
Section: Introductionmentioning
confidence: 99%